Coaching and/or education intervention for parents with overweight/obesity and their children: study protocol of a single-centre randomized controlled trial - Karmali, Shazya (BMC Public Health, 2019)
BACKGROUND: In Canada, a majority of children and adults are insufficiently active for health gains, and about one in seven children and over 20% of adults are overweight or obese. Overweight and obesity are risk factors for many chronic diseases in both adults and children and can result in lower quality and quantity of life. Children whose parents are overweight or obese are more likely to become overweight themselves. Thus, parent/child interventions are important for reducing obesity and promoting long-term healthy weights among members of the family unit. Programs using Co-Active coaching have resulted in positive behaviour changes among adults with overweight/obesity; however, little research has explored the effects of Co-Active coaching on parents, and the consequent impact on the family unit (i.e. all parents and children in the same household). This protocol paper provides a detailed methodological account of a coaching-based program targeting parent and child dyads, in hopes of enhancing health behaviours within the family unit. METHODS: Using a randomized controlled trial design, the researchers aim to identify the impact of coaching plus education (intervention) compared to education only (control) on parents with overweight/obesity and their children (ages 2.5–10, of any weight). A total of 50 dyads are being recruited and randomly assigned using a 1:1 ratio into the control or intervention group. The control group receive 6 webinar-based education sessions focused on physical activity and nutrition. The intervention group receive the same education sessions and nine, 20-min telephone-based sessions with a certified coach. Coaching and health education sessions are conducted with the parent/guardian of the dyad. This paper provides a detailed methodological account of this program. DISCUSSION: The expected findings from this research will advance coaching literature, research, and practice on this topic by determining whether coaching and education are more effective than education alone at producing behaviour changes among a family unit. If proven effective, this approach may be applied more broadly through public health interventionists to parent and child populations in hopes of affecting change with both individuals and their families. TRIAL REGISTRATION: ISRCTN ISRCTN69091372. Retrospectively registered 24 September 2018.